The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s1677-04202008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed fires on the survival and release of seeds of Kielmeyera coriacea (Spr.) Mart. (Clusiaceae) in savannas of Central Brazil

Abstract: Effects of prescribed fires on survival and release of seeds of the woody species Kielmeyera coriacea (Clusiaceae) were investigated in two plots of cerrado sensu stricto, a savanna vegetation of Central Brazil. The first plot was burnt in June, at the beginning of the dry season, and the second in August, in the middle of the dry season. Seed survival was measured after fire in both areas and related to internal and external fruit temperatures measured during the June fire. The proportion of open fruits per i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
2
34
0
10
Order By: Relevance
“…As a vegetation that is susceptible and conditioned by fire (Coutinho 1990), especially savannas and grasslands, this is another factor that can play selective pressure on fruit types in Cerrado. It has been demonstrated that fire increases nutrient cycling on soil and stimulates flowering and thus seed production in some Cerrado plants, such as Poaceae, Cyperaceae and Bromeliaceae (Munhoz & Felfili 2007), and that high temperatures caused by fire can also accelerate fruit drying and seed release and higher germinability in some species, like Kielmeyera coriacea, which have a coriaceous dry fruit (Cirne & Miranda 2008;Zaidan & Carreira 2008). However, there is still little information available about the fire effects on fruit production and germination of the Cerrado species, especially in woody plants (Palermo & Miranda 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a vegetation that is susceptible and conditioned by fire (Coutinho 1990), especially savannas and grasslands, this is another factor that can play selective pressure on fruit types in Cerrado. It has been demonstrated that fire increases nutrient cycling on soil and stimulates flowering and thus seed production in some Cerrado plants, such as Poaceae, Cyperaceae and Bromeliaceae (Munhoz & Felfili 2007), and that high temperatures caused by fire can also accelerate fruit drying and seed release and higher germinability in some species, like Kielmeyera coriacea, which have a coriaceous dry fruit (Cirne & Miranda 2008;Zaidan & Carreira 2008). However, there is still little information available about the fire effects on fruit production and germination of the Cerrado species, especially in woody plants (Palermo & Miranda 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fire may also accelerate fruit drying and thus anticipate the release of the seeds, as recently described in fruits of Kielmeyera coriacea Mart. (Cirne and Miranda 2009). During the fire, fruit surface temperatures as high as 720 o C were measured but maximum internal fruit temperatures were around 60 o C. Mature fruits of K. coriacea have high water content and the evaporation of moisture during exposition to the flames or to the hot air prevent internal temperature from rising above 100 o C until the fruit tissue has dried.…”
Section: Discussionmentioning
confidence: 99%
“…Tal resultado coincide com os registrados em estudos anteriores para Kielmeyera speciosa (Oliveira & Silva 1993;Cirne & Miranda 2008) e Kielmeyera coriacea (Ribeiro et al 1985;Oliveira & Silva 1993;Cirne & Miranda 2008) que apresentaram pico de dispersão de sementes no final da estação seca.…”
Section: Discussionunclassified
“…Estudos anteriores com sementes de Kielmeyera coriacea obtiveram porcentagens de germinação superiores a 60% a 25 °C e fotoperíodo de 12 horas (Oliveira & Silva 1993;Cirne & Miranda 2008). Santana et al (2010) (Melo et al 1979;Botelho & Carneiro 1992;Coelho et al 1997).…”
Section: Discussionunclassified
See 1 more Smart Citation